Evolución y factores determinantes de la Malnutrición Infantil en Imbabura: Evolution and determining factors of Child Malnutrition in Imbabura (La U Investiga, 2019)
Child malnutrition is a problem that is composed of stunting and overweight, which generate effects in the short, medium and long term, affecting the development of the person and society. Ecuador presents a complicated reality of malnutrition, with indicators that are higher than the Latin American average. In this context, the objective of this research is to analyze child malnutrition in Imbabura, its evolution and characteristics. The methodology is quantitative, based on data from the Surveys of Living Conditions 1999-2006-2014, and estimates through probabilistic regressions. Among the main results it is highlighted that child malnutrition in Imbabura is related to environmental, social and personal factors, that have their peculiarities for both stunting and overweight, becoming an invisible enemy, for which public policy is recommended.
Keywords: child malnutrition; child stunting; child overweight; Imbabura; regression analysis